2021
DOI: 10.3390/ani11092483
|View full text |Cite
|
Sign up to set email alerts
|

Modified Spirulina maxima Pectin Nanoparticles Improve the Developmental Competence of In Vitro Matured Porcine Oocytes

Abstract: Molecular approaches have been used to determine metabolic substrates involved in the early embryonic processes to provide adequate culture conditions. To investigate the effect of modified Spirulina maxima pectin nanoparticles (MSmPNPs) on oocyte developmental competence, cumulus–oocyte complexes (COCs) retrieved from pig slaughterhouse ovaries were subjected to various concentrations of MSmPNPs (0, 2.5, 5.0, and 10 µg/mL) during in vitro maturation (IVM). In comparison to the control, MSmPNPs-5.0, and MSmPNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Real-time PCR was performed using a CFX Real-Time PCR System (Bio–Rad, Hercules, CA, USA). The PCR reaction protocol started with initial denaturation at 95 °C for 20 s, 50 °C for 20 s, and 72 °C for 20 s, respectively [ 41 , 42 , 43 ]. After the completion of PCR cycling, we acquired melting curves to verify the specificity and analyzed by 2 − △△Ct method [ 44 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR was performed using a CFX Real-Time PCR System (Bio–Rad, Hercules, CA, USA). The PCR reaction protocol started with initial denaturation at 95 °C for 20 s, 50 °C for 20 s, and 72 °C for 20 s, respectively [ 41 , 42 , 43 ]. After the completion of PCR cycling, we acquired melting curves to verify the specificity and analyzed by 2 − △△Ct method [ 44 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…A CFX Real-Time PCR System was used to conduct the real-time PCR. Initial denaturation for the PCR reaction took place at 95, 50, and 72 °C for 20 s each [ 52 , 53 , 54 ]. The expression levels of the target genes were standardized and normalized in relation to the critical threshold (CT) mean values of rpIU as a housekeeping gene by the 2 − △△Ct method analysis [ 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to many other studies [ 33 35 ], this study showed that ROS was upregulated, and oxidative stress was induced in porcine oocytes as a result of rotenone treatment. In the previous study [ 36 38 ], GSH detected using Cell Tracker was the opposite concept of ROS, and the rotenone treated group decreased compared to the control group. As oxidative stress was speculated to be the result of rotenone-mediated suppression of mitochondrial function, mitochondrial function was also investigated.…”
Section: Discussionmentioning
confidence: 94%